Optimization of Annual and Five Years Tax Payment Services for Motorized Vehicles in Samsat "X" - Ngatilah , Yustina; Siati; Pujiastuti , Caecilia (Nusantara Science and Technology Proceedings)
The Samsat "X" office is a joint service office between the police, the regional income office, and the Jasa Raharja. The services provided are annual and five years of tax payments for motorized vehicles. The current service process is having an uncertain or probabilistic service time and long waiting time, resulting in long queues. This long queue condition causes taxpayer dissatisfaction. One of the methods to solve this problem is the Monte Carlo simulation. Monte Carlo simulation is a simulation method for solving problems with a set of sampling techniques from a probabilistic process. The objective of this research is to determine the optimum number of service personnel by using the Monte Carlo simulation method. The results of this simulation are the optimum conditions (best) for the tax payment services problem at the Samsat "X" office. The result shows that the optimum conditions are obtained with an average waiting time = 22.5479 minutes, an average of service utility level = 81.23%, queue length = 3 persons, and the number of service personnel = 3 persons for annual tax payment services, while for five years tax payment services, the optimum condition for average waiting time = 42.85336 minutes, an average of service utility level = 91.38%, queue length = 5 persons, and the number of service personnel 2 persons.